Pengaruh Board Diversity Dewan Direksi terhadap Sustainability Development pada Perusahaan yang Terdaftar di JII 70 - Rahmatika; Defriko Gusma Putra; Wahyuni Lely Augusna (Universitas Negeri Padang, 2025)
This study analyzes the effect of board diversity (age, gender, educational background, and nationality) on sustainable development in 44 companies included in the Jakarta Islamic Index 70 (JII70) from 2021 to 2024. Using panel data regression analysis (176 observations) in Eviews 12, the Fixed Effect Model was selected as the best estimation model. The test results show that, simultaneously, diversity in age, gender, education, and nationality has a significant effect on sustainability development. Partially, age diversity has a significantly negative effect and gender diversity has a siginificantly positive effect, while education andnationality factors do not show a siginificant effect. The model records a coefficient of determination of 0,064, indicating that board diversity is a statistically siginificant factor, even though sustainability policies are also influenced by other external variables outside the model. These findings confirm the important role of board demographics in strengthening SDGs commitments in thesharia sector.